La cama grande de Sofia - Burke, Tina (La Jolla, Calif. : Kane/Miller Book Pub., 2008)
Sofía loves her crib. But now, she has a new, big bed. It's a very big bed.
"Kane/Miller ubros para los pequnos"--Cover.
Spanish translation of the original English: Sophie's big bed.
Keywords: Beds -- Juvenile fiction; Sleeping customs -- Juvenile fiction; Cribs (Children's furniture) -- Juvenile fiction; Camas -- Novela juvenil